Integrating High-level Questions in Second-Year English Degree Classrooms: Implementation and Challenges - Meriem Kater; Yasmine Boukhedimi (The Journal of Studies in Language, Culture and Society, 2024)
Asking high-level questions is an effective strategy for developing learners’ thinking. Despite the importance of this strategy in promoting and guiding students' thinking, it is found that a great number of teachers ask lower-level questions more than higher-level questions. This is assumed to be due to several challenges related to teachers, students, and other factors. The present research, therefore, attempts to explore the implementation of high-level questions and the challenges that face teachers in incorporating these types of questions in second-year English degree classrooms at the University of Algiers 2. To this end, a mixed-methods approach was adopted using various research methods namely: a questionnaire, an interview, and an observation checklist. The research findings revealed that lower-level questions were used more frequently than higher-level questions. The data obtained from the research tools showed that for the implementation of higher-level questions, the teacher used some techniques such as increasing wait time, repeating the same question several times, and inviting non-volunteering students. Further, it was found that students’ low proficiency, lack of vocabulary, teachers may not be trained to ask high-level questions, as well as large classrooms and lengthy syllabi were the most common challenges. Based on these findings, several pedagogical implications are given. The study recommends a careful planning of questions; matching questions with their purposes; the need to reduce tuition groups; and the need to develop teachers' questioning skills.